Performance and carcass characteristics of Japanese quail fed dietary Cumin (Cuminum cyminum) seed powder as natural feed additive - Challagali, Suma Bala; Dhulipalla, Srinivas Kumar; Pathakamuri, Kavitha; Chappidi, Venkata Seshaiah; R, Sowjanya Lakshmi (Indian Journal of Animal Nutrition, 2021)
An experiment was conducted to evaluate the effect of dietary inclusion of cumin seed (CS) powder on growth, carcass characteristics and cost economics in Japanese quails. One hundred and fifty, day old quail chicks were distributed randomly to five dietary groups each with three replicates of ten chicks and were offered experimental diets to meet the nutrient requirements (NRC, 1994). During the experiment, cumin seed powder is included at 0.0% (T1: Control), 0.50% (T2), 1.0% (T3), 1.5% (T4) and 2.0% (T5) level. Chemical analysis indicated that cumin seed powder contained 18.26% CP, 14.02% EE, 30.02% CF, 27.96% NFE, 7.79% TA and 0.42% AIA. Results indicated that body weight gain, PI (P<0.05) and PER (P<0.01) increased significantly, feed consumed / kg gain (P<0.01) decreased significantly while there was no effect (P>0.05) on feed intake with inclusion of CS powder in the diet. Further, carcass yield (g), dressing percentage and ready to cook yield (g) increased (P<0.01) significantly while there was no effect (P>0.05) on weight of heart, liver, gizzard and giblet. The feed cost / kg gain decreased by4.08 in T2 and7.69 in T3 while it is increased by2.70 in T4, and 8.70 in T5 groups of quails as compared to the control (T1). Thus, it is concluded that cumin seed powder can be included up to 1.0% level in the diet for improved performance of Japanese quail.